ANALYSIS OF ASSOCIATIONS OF VEGF-A GENE POLYMORPHISM AT POSITIONS 2578A/C AND +936C/T WITH DIFFERENT RECEPTOR STATUS IN BREAST CANCER PATIENTS - A. V. Shevchenko; V. I. Konenkov; N. N. Babyshkina; O. V. Savenkova; E. M. Slonimskaya (Сибирский онкологический журнал, 2016)
The study of functional polymorphism of the VEGF-A gene at positions –2578 in the promoter region and +936 in the 3`untranslated region in breast cancer patients with different receptor status of the tumor was undertaken to identify markers associated with risk of breast cancer. DNA samples from 292 women with breast cancer were analyzed. The genotyping of С–2578A and C+936T VEG-FA polymorphisms was performed using the method of restriction analysis of amplification products. The distributions of VEGF-A genotypes in patients having estrogen and progesterone receptors in tumor tissues were investigated and genotypes associated with risk of breast cancer recurrences were detected.